Local structures around the substituted elements in mixed layered oxides - 小林 航; 丹羽 秀治; 守友 浩; Akama Shota; Kobayashi Wataru; Amaha Kaoru; Niwa Hideharu; Nitani Hiroaki; Moritomo Yutaka (Scientific reports, 2017)
The chemical substitution of a transition metal (M) is an effective method to improve the functionality of a material, such as its electrochemical, magnetic, and dielectric properties. The substitution, however, causes local lattice distortion because the difference in the ionic radius (r) modifies the local interatomic distances. Here, we systematically investigated the local structures in the pure (x = 0.0) and mixed (x = 0.05 or 0.1) layered oxides, Na(M1−xM′x)O2 (M and M′ are the majority and minority transition metals, respectively), by means of extended X-ray absorption fine structure (EXAFS) analysis. We found that the local interatomic distance (dM-O) around the minority element approaches that around the majority element to reduces the local lattice distortion. We further found that the valence of the minority Mn changes so that its ionic radius approaches that of the majority M.